Intranasal Dexmedetomidine for the Treatment of Pre-operative Anxiety and Insomnia: A Prospective, Randomized, Controlled, and Clinical Trial - Zeng, Wen; Chen, Li; Liu, Xin; Deng, Xujiang; Huang, Kuan; Zhong, Maolin; Zhou, Shubao; Zhan, Lifang; Jiang, Yulu; Liang, Weidong (Frontiers in Psychiatry, 2022)
Background and objective: Several patients with preoperative anxiety and insomnia refuse to take sleeping pills because of the side effects of sleeping pills. This study aimed to evaluate the applicability of intranasal dexmedetomidine (DEX) in the treatment of preoperative anxiety and insomnia. Methods: A total of 72 patients with insomnia and anxiety were randomly divided into two groups of intranasal DEX (n=36) and intranasal normal saline (NS, n=36). The primary outcomes included patients’ time to fall asleep, total sleep time, insomnia severity index (ISI) after treatment, and satisfaction with the treatment effect. The secondary outcomes were mean arterial pressure (MAP), oxygen saturation (SPO2), heart rate (HR), Narcotrend index (NI) in the first 2 h of treatment, and the incidence of adverse events within 12 h after treatment. Results: The time to fall asleep (22.08±3.95 min) and total sleep time (400.06±28.84 min) in the DEX group were significantly different from those in the NS group (time to fall asleep, 89.31±54.56 min; total sleep time, (295.19±73.51 min; P<0.001). ISI after treatment in the DEX group was lower than that in the NS group (P<0.001). Satisfaction with the treatment effect was better in the DEX group than that in the NS group (P<0.001). The general vital signs in the two groups were stable during the treatment. The drowsiness rate in the NS group was higher than that in the DEX group (P<0.001). Conclusion: Intranasal DEX can significantly improve preoperative anxiety and insomnia.